Fairy gardening ebook Creating your own magical miniature garden. - Bawden-Davis, Julie (2013)
Tabletop Fairy gardens are enjoying an astonishing surge in popularity and now you can begin making your own enchanting miniature landscapes, complete with pint-sized accessories, diminutive plants, and quaint fairy figures. Gardeners Julie Bawden-Davis and Beverly Turner provide you with step-by-step instructions for creating a magical garden that will attract Thumbelina herself! Learn how to design, plant, accessorize, and care for your very own small corner of the world by following seven simple steps, including choosing the perfect container, planting luxurious pint-sized plants, decorating with properly scaled accessories, and telling a story through the delicate fairies you choose to inhabit your magical wonderland. Included are full-color photographs showcasing various types of fairy gardens and accessories, which are sure to inspire the designer in you! And best of all, these perennial gardens are perfect for the busy gardener, as they require less than ten minutes per week to maintain—this could be your new favorite hobby! For the inner child in us all, Fairy Gardening is sure to enchant both the novice and the experienced gardener who wishes to stir up Lilliputian flights of fancy. 75 color photographs Enter a magical, miniature, enchanted fairy land of your own creation!